If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -6y = 15 Solving 9x + -6y = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 9x + -6y + 6y = 15 + 6y Combine like terms: -6y + 6y = 0 9x + 0 = 15 + 6y 9x = 15 + 6y Divide each side by '9'. x = 1.666666667 + 0.6666666667y Simplifying x = 1.666666667 + 0.6666666667y
| 3x-9=60 | | 6v-4v=14-7v+7v | | 7x-18=42 | | -x+x=2x-16 | | 3=b/9+2 | | 10+2x=6x-34 | | 65=-20w-11 | | 8n+6=8+4n+6-4n | | 6(w-2)+2=2(3w-5) | | A-4(2a-7)=3(A+6) | | 7x+2y=-41 | | 27x+54= | | 64x^2=0 | | y=20+8x | | 3x-40+7x-120=180 | | 2(y-1)+4y=3(y-1)+7 | | b+7=2b | | 21=-6+q | | -50+2x=0 | | 0-12=x | | 1*x+0=12 | | -41=.25y+6.9 | | 6y+3=45y-30 | | -98=-7w | | -54=q/62+17 | | z+31/6+z+7/2=12 | | 3x+48=5x | | (4x^2-6x-26)+(7x^2+8x)= | | x^2-14x+y^2+8y=16 | | y=-50+2x | | 3(2p+6)=120 | | -3x^2+3x=-1 |